Exploring Students’ Problems to Interact in English Language in the Classroom at Tertiary Level Education in Rural Areas of Bangladesh (International Journal of Language, Literacy and Translation, 2025)
Speaking is one of the skills that human being use to communicate with one another expressing their ideas. Speaking in English to interact in the classroom with the students and teachers has always been a challenge in rural areas tertiary level education. The aim of this research is to explore the problems of using English to interact in the classroom at English study program in rural areas’ tertiary level education. This research used qualitative research with descriptive qualitative research design. Sixty students participated in this research were chosen by purposive sampling from first semester till seventh semesters at tertiary level of a private university which is situated in a rural area in Bangladesh. Questionnaire consisted of 21 items was distributed to collect the data from the participants. The data analysis shows that there were many problems in using English as the medium for classroom interaction at tertiary level because of some influential factors such as; affective factor, sociocultural factor, age or maturational constrains, aural medium, professional versus academic, environment, learning community. It is difficult to use English in classroom interaction without solving the problems by all the stakeholders. This research will be helpful for future English language instructors and students to overcome the obstacles of using English to interact in the classroom at tertiary level education in rural areas of Bangladesh.